2023
DOI: 10.1111/1365-2656.14017
|View full text |Cite
|
Sign up to set email alerts
|

Predator home range size mediates indirect interactions between prey species in an arctic vertebrate community

Frédéric Dulude‐de Broin,
Jeanne Clermont,
Andréanne Beardsell
et al.

Abstract: Indirect interactions are widespread among prey species that share a common predator, but the underlying mechanisms driving these interactions are often unclear, and our ability to predict their outcome is limited. Changes in behavioural traits that impact predator space use could be a key proximal mechanism mediating indirect interactions, but there is little empirical evidence of the causes and consequences of such behavioural‐numerical response in multispecies systems. Here, we investigate the complex eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 113 publications
0
1
0
Order By: Relevance
“…We showed that predation level on bird nests is the outcome of a complex interaction between temporal fluctuations in lemming populations and spatial variation due to the presence of a large goose colony because both of these factors affect the reproduction, hunting behavior and spatial distribution of foxes (Giroux et al, 2012;Chevallier et al, 2020;Beardsell et al, 2022). Consequently, predation risk for shorebird nests increases when lemming abundance decreases as well as inside the goose colony (Lamarre et al, 2017;Dulude-de Broin et al, 2023), which may ultimately affect the persistence of local shorebird populations (Beardsell et al,…”
Section: Key Scientific Contributionsmentioning
confidence: 99%
“…We showed that predation level on bird nests is the outcome of a complex interaction between temporal fluctuations in lemming populations and spatial variation due to the presence of a large goose colony because both of these factors affect the reproduction, hunting behavior and spatial distribution of foxes (Giroux et al, 2012;Chevallier et al, 2020;Beardsell et al, 2022). Consequently, predation risk for shorebird nests increases when lemming abundance decreases as well as inside the goose colony (Lamarre et al, 2017;Dulude-de Broin et al, 2023), which may ultimately affect the persistence of local shorebird populations (Beardsell et al,…”
Section: Key Scientific Contributionsmentioning
confidence: 99%